A new insight into the profitability of social housing in Australia: A Real Options approach. (November 2020) - Conteh, Augustine; Earl, George; Liu, Benjamin; Roca, Eduardo
Abstract: There is an acute shortage of social housing in Australia; hence, the supply of social housing needs to be increased. The government, however, lacks the necessary resources to adequately respond to this need. Additionally, the level of private institutional investment in social housing is currently low as social housing investments are perceived to be illiquid, high risk, and with low returns. Through a case study on a social housing renewal project in Garbutt, Townsville, Australia, this paper demonstrates that with the application of the Real Option approach, the profitability of the social housing project is actually significantly higher, compared to what they have been shown to be when traditional methods, such as the net present value, are used. This study offers new insight into the profitability of social housing, which has important implications for policymakers and private sector investors and is the first of its kind in the Australian social housing literature.